(untitled) (Revista Electrónica REDINE, 2018)
Organizations today are increasingly concerned with finding methods and strategies aimed at developing competencies in their collaborators that facilitate successful performance. Proper handling of emotions allows people to take charge of their lives and find their personal balance. The present study aimed to analyze the management of emotions as a determinant of educational performance in university education institutions, taking as an illustration the Department of Basic and Social Studies of the Universidad Centroccidental Lisandro Alvarado (UCLA). The work is framed in a field research with a non-experimental design of descriptive level. The technique used for data collection was the survey, for which a questionnaire-type instrument was developed based on a Likert Scale, validated through expert judgment and reliability was measured with Cronbach’s alpha coefficient. The study population consisted of thirty (30) teachers, which were selected in their entirety. For the tabulation and analysis of the data, descriptive statistics were used, the results were presented in tables that included absolute and percentage frequencies for alternative answers, which were illustrated by means of bar graphs. The main findings indicate that the teacher must learn to manage his emotions, be aware of the needs of others, knowing how to develop attention should not only be attentive to your inner reactions, but also to your own reactions. In short, teachers’ knowledge in their area of expertise, pedagogical knowledge and social and emotional skills will result in a teacher with a more effective performance, capable of creating a positive environment for learning.